Electrode material, electrode plate, battery and electric equipment

By using the core-shell structure of nickel-cobalt-manganese material in the positive electrode material of lithium-ion batteries, combined with transition metal-doped lithium manganese ferrophosphate material and conductive agent, the problems of poor stability and large internal resistance of nickel-cobalt-manganese ternary materials are solved, and higher cycle stability and lower internal resistance are achieved.

CN119812234APending Publication Date: 2025-04-11BYD CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410873882.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing nickel, cobalt, manganese ternary materials have poor stability during use, are prone to failure, and have large internal resistance, resulting in poor performance of lithium-ion batteries.

Method used

A new electrode material is used, which includes the core of nickel-cobalt-manganese material, coated with transition metal-doped lithium manganese phosphate material and conductive agent to form a core-shell structure. This structure improves the surface stability of the electrode active substance by reducing the contact between the electrolyte and the nickel-cobalt-manganese material, and reduces the internal resistance of the battery through conductive agent.

Benefits of technology

It improves the cycle stability and safety performance of electrode active substances, reduces the internal resistance of the battery, and enhances the charging and discharging efficiency and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812234A_ABST
    Figure CN119812234A_ABST
Patent Text Reader

Abstract

The invention discloses an electrode material, an electrode plate, a battery and electric equipment. The electrode material comprises an electrode active substance, the electrode active substance comprises an inner core containing a nickel-cobalt-manganese material, a first coating layer coating the inner core and a second coating layer coating the first coating layer, the first coating layer comprises a transition metal doped lithium manganese iron phosphate material, and the second coating layer comprises a transition metal doped lithium manganese iron phosphate material. And the second coating layer comprises a conductive agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage technology, and more specifically, to an electrode material, an electrode sheet, a battery and an electrical device. Background Art

[0002] In the related art, the positive electrode of the lithium-ion battery usually includes a nickel-cobalt-manganese ternary material. However, the existing nickel-cobalt-manganese ternary material has poor stability during use, is prone to failure, and has a large internal resistance.

[0003] Therefore, it is necessary to provide a new technical solution to solve the above technical problems. Summary of the invention

[0004] An object of the present invention is to provide a new technical solution for electrode materials.

[0005] According to a first aspect of the present invention, an electrode material is provided. The electrode material includes an electrode active substance, the electrode active substance includes an inner core containing a nickel-cobalt-manganese material, a first coating layer coated outside the inner core, and a second coating layer coated outside the first coating layer, the first coating layer includes a transition metal-doped lithium manganese iron phosphate material, and the second coating layer includes a conductive agent.

[0006] Optionally, the first coating layer includes a conductive agent, and the transition metal-doped lithium manganese iron phosphate material is mixed with the conductive agent.

[0007] Optionally, along the thickness direction of the electrode active material, the concentration of the transition metal-doped lithium manganese iron phosphate material in the first coating layer gradually decreases from a side close to the core to a side close to the second coating layer.

[0008] Optionally, the transition metal oxide comprises a divalent transition metal oxide.

[0009] Optionally, the divalent transition metal oxide includes at least one of beryllium oxide, magnesium oxide and calcium oxide.

[0010] Optionally, the conductive agent comprises a carbon material.

[0011] Optionally, the carbon material includes at least one of a point-shaped carbon material and a line-shaped carbon material.

[0012] Optionally, the molar ratio of manganese to iron is x:(1-x), wherein x=0.3 to 0.9.

[0013] Optionally, in the transition metal-doped lithium iron manganese phosphate material, a molar ratio of transition metal oxide to lithium iron manganese phosphate material is 0.1% to 10%.

[0014] Optionally, it further comprises: a conductive material, wherein the conductive material is mixed with the electrode active material.

[0015] Optionally, the conductive material includes linear conductive material and dot conductive material.

[0016] Optionally, based on parts by mass, the electrode active material is 90 parts to 97 parts, the point-shaped conductive material is 1.8 parts to 2 parts, the linear conductive material is 0.02 parts to 0.2 parts, and the binder is 1 part to 3 parts.

[0017] Optionally, the density of the electrode material is 2.3 g / cm 3 Up to 2.6g / cm 3 .

[0018] According to a second aspect of the present application, an electrode sheet is provided, which includes a current collector and the electrode material described in the present application, wherein the electrode material is attached to the surface of the current collector.

[0019] According to a third aspect of the present application, a battery is provided, which includes the electrode sheet described in the present application.

[0020] Optionally, the electrode sheet is a positive electrode sheet, and the battery further includes a negative electrode sheet, a separator and an electrolyte, the separator is located between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet, the negative electrode sheet and the separator are immersed in the electrolyte.

[0021] Optionally, the electrolyte includes an electrolyte solvent, a lithium salt and an additive, the lithium salt and the additive are dissolved in the electrolyte solvent, and the additive includes fluoroethylene carbonate.

[0022] Optionally, the additive further includes at least one of methylene methanedisulfonate, trimethylsilyl phosphate, triphenyl phosphate, vinylene carbonate, vinyl sulfate, and (ethoxy) pentafluorocyclotriphosphazene.

[0023] Optionally, the additive further includes methylene methanedisulfonate, trimethylsilyl phosphate and triphenyl phosphate.

[0024] Optionally, the mass percentage of each substance in the electrolyte is: methylene methanedisulfonate is 1% to 3%, trimethylsilyl phosphate is 0.5% to 1.5%, and triphenyl phosphate is 0.5% to 1.5%.

[0025] Optionally, the additive further comprises vinylene carbonate, vinyl sulfate and (ethoxy) pentafluorocyclotriphosphazene.

[0026] Optionally, the mass percentages of the various substances in the electrolyte are: 0.5% to 1.5% for vinylene carbonate, 0.5% to 1.5% for vinyl sulfate, and 0.1% to 0.8% for (ethoxy) pentafluorocyclotriphosphazene.

[0027] Optionally, the electrolyte solvent includes cyclic carbonate and chain carbonate.

[0028] Optionally, the cyclic carbonate includes at least one of ethylene carbonate and propylene carbonate.

[0029] Optionally, the linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.

[0030] According to a fourth aspect of the present application, an electrical device is provided, which includes the battery described in the present application.

[0031] According to one embodiment of the present application, the positive electrode material includes an electrode active material. The electrode active material includes an inner core and two coating layers coated outside the inner core. The two coating layers can effectively reduce the contact between the electrolyte and the nickel-cobalt-manganese material, improve the surface stability of the electrode active material, and effectively inhibit the exothermic reaction between the electrolyte and the nickel-cobalt-manganese material under abuse conditions such as overcharging, short circuit, heating and acupuncture, thereby improving the cycle stability and safety performance of the electrode active material. The conductive agent can improve the conductivity of the electrode active material and reduce the internal resistance of the battery.

[0032] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.

[0034] Figure 1 It is a schematic diagram of the structure of the positive electrode material according to an embodiment of the present application.

[0035] Figure 2 yes Figure 1 A partial enlarged view of .

[0036] Figure 3 This is the SOC-OCV curve of the battery according to the embodiment of the present application at a rate of 0.05C.

[0037] Figure 4 is a SOC-DCIR curve of a battery according to an embodiment of the present application at room temperature.

[0038] Figure 5It is the charge and discharge energy retention rate of the battery according to the embodiment of the present application at different rates at room temperature.

[0039] Figure 6 It is the discharge retention rate of the battery according to the embodiment of the present application at different temperatures.

[0040] Description of reference numerals:

[0041] 1. inner core; 2. first coating layer; 2-1. high concentration layer; 2-2. low concentration layer; 2-3. carbon material; 3. second coating layer. DETAILED DESCRIPTION

[0042] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.

[0043] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.

[0044] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.

[0045] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0046] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.

[0047] According to one embodiment of the present application, an electrode material is provided. The electrode material includes an electrode active substance. The electrode active substance includes an inner core 1 containing a nickel-cobalt-manganese material, a first coating layer 2 coated outside the inner core 1, and a second coating layer 3 coated outside the first coating layer 2, wherein the first coating layer 2 includes a transition metal-doped lithium manganese iron phosphate material, and the second coating layer 3 includes a conductive agent.

[0048] like Figure 1 , Figure 2As shown, the electrode active material is used as a positive electrode active material. The electrode material is coated on a metal foil to form an electrode sheet. The electrode active material is a core-shell structure. The inner core 1 is a ternary material, i.e., a nickel-cobalt-manganese material. Optionally, the ternary material includes at least one of NCM111, NCM523, NCM622, and NCM811. The first coating layer 2 is coated outside the inner core 1. Transition metal-doped lithium manganese iron phosphate (LiMnPO4, referred to as LMP) material combines the stability and high voltage characteristics of the olivine phosphate structure. By doping with different transition metal oxides, the lithium manganese iron phosphate material can obtain better electrochemical properties, such as high structural stability, electrical conductivity, and cycle performance. The second coating layer 3 is a conductive agent. The conductive agent is used for electrical conduction, which can increase the electron conduction path inside the electrode active material, reduce the internal resistance of the battery, improve the charge and discharge efficiency of the battery, and can also improve the rate performance and cycle stability of the battery. The conductive agent helps to reduce the polarization of the electrode reaction, reduce energy loss, and increase the operating voltage of the battery.

[0049] The electrode active material is in a granular form. The average particle size of the core-shell structure is less than or equal to 10 μm. Within this range, the core-shell structure has high structural strength and excellent electrochemical performance. Further, the average particle size is 200 nm to 2 μm, within this range, the electrochemical performance of the electrode active material is even better.

[0050] The thickness of the first coating layer 2 is 1 nm to 100 nm, preferably 10 nm to 80 nm. The thickness of the second coating layer 3 is 10 nm to 50 nm, preferably 20 nm to 35 nm. Within the above range, the two coating layers provide good protection for the core 1.

[0051] In the embodiment of the present application, the electrode material includes an electrode active substance. The electrode active substance includes an inner core 1 and two coating layers coated outside the inner core 1. The two coating layers can effectively reduce the contact between the electrolyte and the nickel-cobalt-manganese material, improve the surface stability of the electrode active substance, and effectively inhibit the exothermic reaction between the electrolyte and the nickel-cobalt-manganese material under abuse conditions such as overcharging, short circuit, heating and acupuncture, thereby improving the cycle stability and safety performance of the electrode active substance.

[0052] In one example, the electrode material further includes a conductive substance, which is mixed with the electrode active substance. The conductive substance can form a continuous conductive network between the granular electrode active substances, thereby increasing the electron conduction rate of the electrode material, so that the electrons generated during the charge and discharge process can be quickly transferred to the current collector and then enter the external circuit. The conductive substance fills the pores between the granular electrode active substances, effectively reducing the contact resistance between the electrode active substances and the current collector, enhancing the conductivity of the electrode sheet, and reducing the power loss caused by excessive resistance.

[0053] In addition, the conductive material helps to evenly coat the positive electrode slurry, making the distribution of the electrode active material in the current collector more uniform, improving the balance and stability of the overall battery performance. The conductive material can also provide a certain mechanical support to maintain the structural integrity of the electrode sheet during multiple charge and discharge cycles, prevent the electrode active material from falling off, and extend the battery life.

[0054] In one example, the electrode material also includes a binder, which can firmly bind the positive electrode active material, the conductive material and the current collector together to form a stable electrode sheet, preventing the electrode active material from falling off or aggregating from the current collector during the battery charge and discharge cycle, thereby ensuring the integrity and stability of the electrode. The binder can also form effective contact between the electrode active material particles, promote the transfer of electrons, and ensure that the current can flow smoothly inside the electrode material. During the operation of the battery, the electrode active material may undergo volume changes. The cured binder is elastic and can buffer the volume changes of the electrode active material to a certain extent, reduce stress, maintain the integrity of the electrode sheet, and improve the cycle life of the battery.

[0055] In one example, the conductive material includes a linear conductive material and a dot conductive material. Both of the above materials can improve the conductivity and service life of the electrode material and reduce the resistance of the electrode material.

[0056] For example, the point-shaped conductive material includes at least one of carbon black, acetylene black, Ketjen black and conductive graphite. The linear conductive material includes at least one of carbon fiber and carbon nanotube. The linear conductive material has high strength and toughness, which can improve the mechanical properties of the electrode material and prevent the deformation or breakage of the electrode material during the charging and discharging process. The addition of the point-shaped conductive material can also further enhance the structural stability of the electrode material. The mixed linear conductive material and the point-shaped conductive material can effectively reduce the internal resistance of the electrode material, improve the charging and discharging efficiency of the battery, and increase the energy density of the battery.

[0057] In one example, based on parts by mass, the electrode active material is 90 parts to 97 parts, the point-shaped conductive material is 1.8 parts to 2 parts, the linear conductive material is 0.02 parts to 0.2 parts, and the binder is 1 part to 3 parts.

[0058] In this example, by adjusting the added amounts of the positive electrode active material, the point-shaped conductive material, the line-shaped conductive material and the binder, the electrode material has a high energy density, a low internal resistance, good cycle performance and a long service life.

[0059] In one example, the density of the electrode material is 2.3 g / cm 3 Up to 2.6g / cm 3 .

[0060] The higher the density of the electrode material, the more electrode active substances can be accommodated in the same volume, thus achieving a higher energy density. However, too high a density may cause the contact between the electrode active material particles to be too close, hindering the penetration of the electrolyte and the diffusion of lithium ions, affecting the cycle stability and long-term performance of the battery. In addition, too high a density will also increase the internal stress of the electrode sheet, leading to structural damage to the electrode sheet and the shedding of the electrode active material.

[0061] The above density range enables the electrode material to have a high energy density and can significantly improve the cycle stability, structural stability and service life of the battery.

[0062] In one example, the first coating layer 2 includes a conductive agent, and the transition metal-doped lithium manganese iron phosphate material is mixed with the conductive agent.

[0063] In this example, transition metal-doped lithium manganese iron phosphate material forms particles. The gaps between the particles are filled with a conductive agent. The conductive agent can further increase the electron conduction path inside the electrode active material, reduce the internal resistance of the battery, improve the charge and discharge efficiency of the battery, and improve the rate performance and cycle stability of the battery.

[0064] Furthermore, the nickel-cobalt-manganese material as the core 1 is formed into particles. Conductive agent is also filled between the particles. This arrangement can further reduce the internal resistance of the battery, improve the charge and discharge efficiency of the battery, and improve the rate performance and cycle stability of the battery.

[0065] In one example, the conductive agent includes carbon material 2-3. Carbon material 2-3 has good conductivity and can form a good combination with nickel-cobalt-manganese material and transition metal-doped lithium manganese iron phosphate material.

[0066] Of course, the conductive agent is not limited to the carbon material 2-3, and may also be a conductive polymer, etc. Those skilled in the art may set it according to actual needs.

[0067] In one example, the carbon material 2-3 includes at least one of a point-shaped carbon material and a line-shaped carbon material.

[0068] Optionally, the point-shaped carbon material includes at least one of carbon black, acetylene black, Ketjen black and conductive graphite. The linear carbon material includes at least one of carbon fiber and carbon nanotube. The linear carbon material has high strength and toughness, can improve the mechanical properties of the electrode active material, and prevent deformation or breakage of the electrode active material during charging and discharging. The addition of the point-shaped carbon material can also further enhance the structural stability of the electrode active material.

[0069] Preferably, the carbon material 2-3 includes point-shaped carbon material and linear carbon material. Since the linear carbon material and point-shaped carbon material have excellent conductivity, mixing them together can effectively reduce the internal resistance of the electrode active material, improve the charge and discharge efficiency of the battery, and increase the energy density of the battery.

[0070] Of course, the carbon materials 2-3 are not limited to the above embodiments, and those skilled in the art can configure them according to actual needs.

[0071] In one example, along the thickness direction of the electrode active material, the concentration of the transition metal-doped lithium manganese iron phosphate material in the first coating layer 2 gradually decreases from the side close to the core 1 to the side close to the second coating layer 3 .

[0072] In this example, the concentration of the transition metal-doped lithium iron manganese phosphate material in the first coating layer 2 gradually decreases from the inside to the outside. The concentration of the conductive agent in the first coating layer 2 gradually increases from the inside to the outside. In this way, the closer the first coating layer 2 is to the outer layer, the better the electron transport performance, thereby effectively improving the conductivity of the electrode active material. The closer the first coating layer 2 is to the inner layer, the higher the concentration of the lithium iron manganese phosphate material and the higher the energy density. In this way, the electrode active material can effectively take into account both high energy density and high conductivity.

[0073] For example, Figure 1 to Figure 2 As shown, the portion of the first coating layer 2 close to the core 1 forms a high concentration layer 2-1, and the portion close to the second coating layer 3 forms a low concentration layer 2-2. The concentration of the transition metal-doped lithium manganese iron phosphate material in the high concentration layer 2-1 is high. The concentration of the transition metal-doped lithium manganese iron phosphate material in the low concentration layer 2-2 is low. The electrode active material can more effectively take into account both high energy density and high conductivity.

[0074] In one example, the transition metal oxide includes a divalent transition metal oxide.

[0075] In this example, the divalent transition metal oxide introduced into the lithium manganese iron phosphate material can play a doping and modification role on the lithium manganese iron phosphate material, so that the ion conductivity of the lithium manganese iron phosphate material is significantly improved.

[0076] In addition, the divalent transition metal-doped lithium iron manganese phosphate material will form nano metal oxides, such as nano-sized divalent transition metal oxides, on the surface of the lithium iron manganese phosphate. During the annealing treatment, the nano-sized divalent transition metal oxides react with the residual lithium carbonate, lithium hydroxide and other materials on the surface of the lithium iron manganese phosphate material to form a lithium ion conductor, thereby reducing the residual alkali content of the lithium iron manganese phosphate material, and improving the ability of the lithium iron manganese phosphate material to conduct lithium ions, and enhancing the bonding force between the first coating layer 2 and the second coating layer 3.

[0077] Optionally, the divalent transition metal oxide includes at least one of beryllium oxide, magnesium oxide and calcium oxide.

[0078] In this example, the above materials have good stability, can effectively reduce the residual alkali content of the lithium manganese iron phosphate material, improve the ability of the lithium manganese iron phosphate material to conduct lithium ions, and enhance the bonding force between the first coating layer 2 and the second coating layer 3.

[0079] In one example, the molar ratio of manganese to iron is x:(1-x), wherein x=0.3 to 0.9.

[0080] In this example, the general formula of lithium manganese iron phosphate material is LiMn x Fe 1-x PO4. For example, x is 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9. Within this range, the manganese content in the first coating layer 2 is further reduced, the manganese dissolution amount is reduced, and the performance of the first coating layer 2 is ensured to be stable.

[0081] In one example, in the transition metal-doped lithium manganese iron phosphate material, the molar ratio of the transition metal to the lithium manganese iron phosphate material is 0.1% to 10%.

[0082] Within this range, the divalent transition metal oxide can effectively reduce the residual alkali content of the lithium manganese iron phosphate material, improve the ability of the lithium manganese iron phosphate material to conduct lithium ions, and enhance the bonding force between the first coating layer 2 and the second coating layer 3 .

[0083] In one example, the method for preparing the electrode active material includes:

[0084] Mixing the raw materials of the transition metal oxide and the lithium iron manganese phosphate material, and performing a first calcination to obtain a first material;

[0085] Mixing the first material, the core and the first conductive agent to obtain a second material, wherein the second material includes the core and a first coating layer 2 coated outside the core;

[0086] A second coating layer 3 is formed outside the first coating layer 2, wherein the second coating layer includes a conductive agent.

[0087] In an embodiment of the present application, the core 1 is a ternary material, such as a nickel-cobalt-manganese material. Optionally, the ternary material includes at least one of NCM111, NCM523, NCM622, and NCM811. The core 1 is a powder, and the particle size of the core 1 is micrometer-level. Optionally, the particle size of the core 1 is less than or equal to 5μm. Further, the particle size of the core 1 is 0.5μm to 1μm. Within this range, the core 1 has high activity and high electrochemical stability. The first coating layer 2 is coated on the outside of the core 1 and the second coating layer 3 is coated on the outside of the first coating layer 2 by physical coating. Transition metal-doped lithium manganese iron phosphate (LiMnPO4, referred to as LMP) material combines the stability of the olivine phosphate structure and the high voltage characteristics. By doping with different transition metal oxides, the lithium manganese iron phosphate material can obtain better electrochemical properties, such as high structural stability, electrical conductivity and cycle performance. The second coating layer 3 is a conductive agent. Conductive agents are used for conducting electricity, which can increase the electron conduction path inside the electrode material, reduce the internal resistance of the battery, improve the charge and discharge efficiency of the battery, and improve the rate performance and cycle stability of the battery. Conductive agents help reduce the polarization of the electrode reaction, reduce energy loss, and increase the operating voltage of the battery. The preparation method has a simple process and can form an electrode material with stable properties.

[0088] In one example, the step of coating the core 1 to form a first coating layer 2, wherein the first coating layer 2 includes a transition metal-doped lithium manganese iron phosphate material, includes:

[0089] Mixing the raw materials of the transition metal oxide and the lithium iron manganese phosphate material, and performing a first calcination to obtain a first material;

[0090] The first material, the core 1 and the first conductive agent are mixed to obtain a second material, wherein the second material includes the core 1 and a first coating layer 2 coating the core 1 .

[0091] In this example, the raw materials of the lithium iron manganese phosphate material include a lithium source, a manganese source, an iron source and a phosphorus source. Optionally, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium chloride and lithium oxide. The manganese source includes at least one of manganese dioxide, manganese tetraoxide and manganese sulfate. The iron source includes at least one of ferrous sulfate, ferric nitrate, iron oxide, iron powder, ferrous oxalate and ferrous phosphate. The phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate or diammonium hydrogen phosphate. Transition metal oxides are used to provide transition metal elements. Transition metal oxides are introduced in the process of preparing the lithium iron manganese phosphate material. Transition metal oxides can dope and modify the lithium iron manganese phosphate material, thereby improving the ion conductivity of the lithium iron manganese phosphate material. In addition, the transition metal oxides will also form nano metal oxides on the surface of the lithium iron manganese phosphate material. During the annealing treatment, the transition metal oxide reacts with the residual lithium carbonate, lithium hydroxide and other substances on the surface of the lithium iron manganese phosphate material to form a lithium ion conductor, thereby reducing the residual alkali content of the lithium iron manganese phosphate material, improving the ability of the lithium iron manganese phosphate material to conduct lithium ions, and enhancing the bonding force between the first coating layer 2 and the second coating layer 3. After the first calcination, a transition metal-doped lithium iron manganese phosphate material, i.e., the first material, can be formed.

[0092] During coating, the first material, the core 1 and the first conductive agent are mixed to obtain the second material, wherein the second material includes the core 1 and the first coating layer 2 coated outside the core 1. It should be noted that the particle size of the core 1 is less than or equal to 5μm. Furthermore, the particle size of the core 1 is 0.5μm to 1μm. The first material is a granular material, and its particle size is nanometer-level. For example, the particle size of the first material is less than or equal to 100μm. Since the particle size of the core 1 is larger than that of the first material, the first material can adhere to the surface of the core 1 during the mixing process. Preferably, the particle size of the first material is greater than or equal to 40μm. This particle size range is not only convenient for the coating of the first coating layer 2 on the core, but also convenient for the coating of the second coating layer 3 on the first coating layer 2.

[0093] Preferably, in order to improve the conductivity of the first material. The raw material of the lithium manganese iron phosphate material also includes a first carbon-containing organic matter. The first carbon-containing organic matter includes at least one of glucose, sucrose, fructose, cellulose, starch, etc. In order to mix evenly, the raw material of the lithium manganese iron phosphate material is added to the first solvent. The first solvent includes at least one of ketones, alcohols, and water. Ketones include acetone, methyl ethyl ketone, butanone, cyclohexanone, etc. Alcohols include methanol, ethanol, propanol, ethylene glycol, etc. During preparation, the above materials are added to the first solvent and mixed. For example, mixing is performed by ultrasonic dispersion, mechanical stirring, etc.

[0094] Finally, the mixed liquid is first calcined in a muffle furnace, for example, in a nitrogen or inert gas atmosphere, to obtain a first material.

[0095] In one example, the step of forming the second coating layer 3 outside the first coating layer 2, wherein the second coating layer 3 includes a conductive agent, comprises:

[0096] The second carbon-containing organic matter and the second material are mixed and calcined for a second time to obtain the electrode material, which includes a core 1 , a first coating layer 2 coated outside the core 1 , and a second coating layer 3 coated outside the first coating layer 2 .

[0097] In this example, the second carbon-containing organic matter includes at least one of glucose, sucrose, fructose, cellulose, starch, etc. The above substances can form a coating on the second material. After the second calcination, the second carbon-containing organic matter forms a conductive agent, and the conductive agent forms a second coating layer 3, and the second coating layer 3 is coated on the outside of the first coating layer 2. The conductive agent is a granular material. The particle size of the conductive agent is 20μm to 35μm. The particle size of the conductive agent is smaller than the particle size of the first material, so the second coating layer 3 can be coated on the outside of the first coating layer 2.

[0098] In one example, in the manganese source and the iron source, the molar ratio of manganese to iron is x:(1-x), wherein x=0.3 to 0.9.

[0099] In this example, the general formula of lithium manganese iron phosphate material is LiMn x Fe 1-x PO4. For example, x is 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9. Within this range, the manganese content in the first coating layer 2 is further reduced, the manganese dissolution amount is reduced, and the performance of the first coating layer 2 is ensured to be stable.

[0100] In one example, the step of adding a lithium source, a manganese source, an iron source, a phosphorus source, a transition metal oxide, and a first carbon-containing organic matter into a first solvent for mixing, and performing a first calcination to obtain a first material includes:

[0101] Adding a lithium source, a manganese source, an iron source and a phosphorus source into a first solvent for dissolving to obtain a first mixed solution;

[0102] dissolving a transition metal oxide and a first carbon-containing organic matter in the first mixed solution to obtain a second mixed solution;

[0103] The second mixed solution is subjected to a first calcination to obtain a first material.

[0104] In this example, multiple raw materials are added in steps. For example, in the step of adding a lithium source, a manganese source, an iron source, and a phosphorus source to a first solvent for dissolution to obtain a first mixed solution, the above materials are easily dispersed in the first solvent, so the lithium source, the manganese source, the iron source, and the phosphorus source are added to the first solvent for dissolution at room temperature.

[0105] In the step of adding the lithium source, manganese source, iron source and phosphorus source to the first solvent for dissolution to obtain the first mixed solution, the transition metal oxide and the first carbon-containing organic matter are not easy to disperse in the first mixed solution, so under heating conditions, the transition metal oxide and the first carbon-containing organic matter are dispersed in the first mixed solution to obtain a second mixed solution. For example, the heating temperature is 60°C. The ultrasonic dispersion time is 0.5 hours to 1 hour. Of course, the heating temperature is not limited to 60°C, and can also be 50°C, 70°C, 80°C, etc. Those skilled in the art can set it according to actual needs.

[0106] Finally, the second mixed solution is added into the muffle furnace for the first calcination.

[0107] The first material is mixed by a multi-step dispersion method, and the quality of the final obtained first material is uniform.

[0108] In one example, the molar ratio of the transition metal oxide, the first carbon-containing organic matter and the lithium manganese iron phosphate is a, a / 3, wherein a=0.03 to 0.2.

[0109] Within this range, the transition metal oxide can effectively dope and modify the lithium manganese iron phosphate, and the first carbon-containing organic matter can enable the transition metal-doped lithium manganese iron phosphate material to form a nanomaterial.

[0110] In one example, the temperature of the first calcination is 400° C. to 950° C., and the temperature is maintained for 1 to 3 hours when the temperature is raised to the full temperature.

[0111] In this example, the first sintering temperature is within this range, which can make the transition metal doped lithium manganese iron phosphate material form nanomaterials. During the heating process, the muffle furnace is kept warm for 1 to 3 hours when the temperature rises to the full temperature. Insulation can ensure that the transition metal oxide, the first carbon-containing organic matter and the lithium manganese iron phosphate have enough time to fully react chemically at the set high temperature to form the desired compound phase. Insulation can promote the growth of the lattice of the transition metal doped lithium manganese iron phosphate material and improve the crystallinity of the material. High crystallinity helps the rapid diffusion of lithium ions. Insulation helps to form a more stable crystal structure, which can effectively improve the electrochemical performance and cycle stability of the material. Insulation can also reduce the thermal stress caused by rapid cooling, reduce the microstructural defects of the crystal structure, reduce the thermal decomposition of the material at high temperature, and maintain the chemical stability of the material. The length of the insulation time can control the microstructure of the material, including the size and shape of the grains. Insulation also helps to increase the density of the sintered body, reduce pores, and improve the energy density and power density of the battery.

[0112] For example, the temperature of the first sintering is 800°C. During the sintering process, in a nitrogen atmosphere, the temperature is stepped to 800°C at a temperature rise rate of 5°C / minute. After natural cooling, the first material is obtained, wherein the temperature step has a critical value of a whole temperature number such as 200°C to 400°C. Insulation is performed in multiple steps. For example, the room temperature is 25°C→200°C→400°C→600°C→800°C. The temperature is maintained at a constant level for 2 hours at each step. That is, the temperature is maintained at 200°C, 400°C, 600°C, and 800°C for 2 hours each. In this way, the generated transition metal-doped lithium manganese iron phosphate material has a good crystal form, few defects, small thermal stress, dense material density, good chemical stability, and high energy density and power density.

[0113] In other examples, the temperature may be kept at 100° C., 300° C., 500° C., 700° C., or 800° C. Alternatively, the temperature may be kept at 200° C., 300° C., 600° C., 700° C., or 800° C. The temperature of the keeping temperature may be set according to actual needs.

[0114] Of course, the temperature and heat preservation process of the first calcination are not limited to the above embodiments, and those skilled in the art can set them according to actual needs.

[0115] In one example, the step of mixing the first material, the core 1 and the first conductive agent to obtain the second material includes:

[0116] Dissolving part of the first material, the nickel-cobalt-manganese material, and the first conductive agent in the second solvent, and mixing them by ultrasonic dispersion to obtain a third mixed solution;

[0117] ball milling the third mixed solution;

[0118] The third mixed solution after ball milling is spray-dried.

[0119] In this example, the nickel-cobalt-manganese material includes at least one of NCM111, NCM523, NCM622, and NCM811. The first conductive agent may be, but is not limited to, carbon material 2-3. The second solvent includes at least one of ketone, alcohol, and water. After the first material, the nickel-cobalt-manganese material, and the first conductive agent are added to the second solvent, they are mixed by mechanical stirring, ultrasonic dispersion, and the like. The mixed solution is dried by spray drying, heating drying, and the like. After drying, the second material is obtained. In the step of dissolving part of the first material, the nickel-cobalt-manganese material, and the first conductive agent in the second solvent and mixing them by ultrasonic dispersion to obtain a third mixed solution, the second solvent is ethanol. Part of the first material, the nickel-cobalt-manganese material, and the first conductive agent are dissolved in ethanol. For example, at 60°C, ultrasonic dispersion is performed for 0.5 to 1 hour to finally obtain a third mixed solution.

[0120] In the step of ball milling the third mixed solution, the third mixed solution is ball milled. For example, the third mixed solution is added to a ball milling jar and ball milled for 2 hours. The ball milling speed is 300 rpm to 600 rpm, and the number of ball milling is 2 or 3 times.

[0121] Ball milling reduces the particle size of the raw material powder through mechanical force to form fine primary particles, which helps to increase the specific surface area of ​​the material, thereby increasing the diffusion rate of lithium ions and improving the charge and discharge rate of the battery. Ball milling can promote the occurrence of solid-state reactions, especially in the second calcination, ball milling can increase the reaction rate and help synthesize electrode materials with specific structures and properties. Ball milling can increase the compaction density of electrode materials, reduce the gaps between particles, and help improve the energy density of batteries. Ball milling can introduce more defects and grain boundaries, which can serve as rapid diffusion channels for lithium ions and improve the conductivity of electrode materials.

[0122] Finally, the third mixed solution after ball milling is spray dried. By adjusting the parameters of spray drying, such as spray speed, hot air temperature, drying rate, etc., the particle morphology and size of the obtained electrode material powder can be controlled, thereby affecting the charge and discharge performance of the electrode material. The particles produced by spray drying usually have a smaller size and a higher specific surface area, which helps to increase the diffusion rate of lithium ions, thereby improving the charge and discharge efficiency of the battery. Spray drying can prepare electrode materials with good electrochemical properties, such as high capacity, high rate performance and excellent cycle stability.

[0123] In one example, it also includes:

[0124] adding another portion of the first material, the second material, and the second conductive agent into the third solvent, and mixing them by ultrasonic dispersion to obtain a fourth mixed solution;

[0125] ball milling the fourth mixed solution;

[0126] The fourth mixed solution after ball milling is spray-dried.

[0127] In this example, the second conductive agent includes carbon material 2-3. The third solvent includes at least one of ketone, alcohol, and water. Another part of the first material, the second material, and the second conductive agent are added to the third solvent and mixed by mechanical stirring, ultrasonic dispersion, etc. The mixed solution is dried by spray drying, heating drying, etc. After drying, the second material is obtained.

[0128] In the step of adding another portion of the first material, the second material, and the second conductive agent to the third solvent and mixing them by ultrasonic dispersion to obtain a fourth mixed solution, the third solvent is ethanol. The first material, the second material, and the second conductive agent are added to ethanol and dissolved. Ultrasonic dispersion is performed at 60° C. for 1 to 2 hours to finally obtain a fourth mixed solution.

[0129] In the step of ball milling the fourth mixed solution, the fourth mixed solution is ball milled. For example, the fourth mixed solution is added to a ball milling jar and ball milled for 2 hours. The ball milling speed is 300 to 600 rpm, and the number of ball millings is 2 or 3 times.

[0130] In the step of spray-drying the fourth mixed solution after ball milling, the fourth mixed solution after ball milling is spray-dried to obtain the second material.

[0131] In this example, by adding the first material twice, the second coating layer 3 can be formed into the high-concentration layer 2 - 1 and the low-concentration layer 2 - 2 .

[0132] Of course, more concentration gradient layers can be formed by adding the first material more times.

[0133] In one example, in the step of mixing the second carbon-containing organic matter and the second material and performing a second calcination to obtain the electrode material, the molar ratio of the second carbon-containing organic matter to the second material is b, where b=0.01 to 0.15.

[0134] Optionally, the second carbon-containing organic matter includes at least one of glucose, sucrose, fructose, cellulose, starch, etc. The fourth solvent includes at least one of ketone, alcohol, and water. Ketones include acetone, methyl ethyl ketone, butanone, cyclohexanone, etc. Alcohols include methanol, ethanol, propanol, ethylene glycol, etc. After the second material and the second carbon-containing organic matter are added to the fourth solvent, they are mixed by mechanical stirring, ultrasonic dispersion, etc. The mixed solution is added to a muffle furnace and calcined for the second time in an inert gas or nitrogen atmosphere. After the second calcination, the electrode material described in the present application is obtained.

[0135] For example, the second carbon-containing organic matter is glucose. The fourth solvent is ethanol. For example, the solution after the second material, the second carbon-containing organic matter and the fourth solvent are mixed is ultrasonically dispersed at 60° C. for 1 to 2 hours. Then, the ultrasonically dispersed solution is placed in a muffle furnace for a second calcination.

[0136] The molar ratio of the second carbon-containing organic matter to the second material is b, b=0.01 to 0.15. For example, the molar ratio of glucose to the second material is 0.01 to 0.15. Glucose is converted into carbon material 2-3 during high-temperature calcination. Carbon material 2-3 acts as a conductive agent, i.e., the second coating layer 3. Within this range, the thickness of the second coating layer 3 is uniform and has few defects. For example, when the thickness is within the above thickness range, the second coating layer 3 significantly improves the electrical conductivity of the electrode material, thereby reducing the internal resistance of the battery. The second coating layer 3 can serve as a protective layer, reducing the side reactions of the electrode material with the electrolyte during the charge and discharge process, thereby improving the cycle stability of the battery. The second coating layer 3 helps to form a stable chemical and electrochemical reaction interface on the surface of the electrode material, reducing the decomposition of the electrolyte. The second coating layer 3 can also buffer the volume change of the electrode material during the charge and discharge process, reduce structural stress, and improve the structural stability of the electrode material.

[0137] In one example, the second calcination temperature is 700° C. to 1000° C., and when the temperature rises to an integer multiple of 100, the temperature is maintained for 0.5 hour to 1.5 hours.

[0138] In this example, the calcination atmosphere of the muffle furnace is nitrogen, and the temperature is increased stepwise to 700°C at a temperature increase rate of 5°C / min. The temperature is kept at 700°C. After natural cooling, the electrode material is obtained. In the second calcination process, for example, the room temperature is 25°C. The temperature increase process is 25°C→100°C→200°C→300°C→400°C→500°C→600°C→700°C. At each step, i.e., 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, and 700°C, each temperature is kept constant for 1 hour, and finally the electrode material is obtained.

[0139] In this example, through the second calcination, a core-shell structure electrode material containing a core 1 of nickel-cobalt-manganese material, a transition metal-doped lithium manganese iron phosphate material as a first coating layer 2, and a conductive agent as a second coating layer 3 is finally obtained.

[0140] Of course, in the above steps, when performing ultrasonic dispersion, the heating temperature is not limited to 60°C, but can also be 50°C, 70°C, 80°C, etc. Those skilled in the art can set it according to actual needs. According to the second embodiment of the present application, an electrode sheet is provided. The electrode sheet includes a current collector and the electrode material described in the present application. The electrode material is attached to the surface of the current collector.

[0141] The current collector is a metal foil. The material of the current collector is copper, aluminum, nickel, silver, etc. The electrode material is mixed with a fifth solvent to prepare a slurry. The fifth solvent is at least one of N-methylpyrrolidone, butanone, cyclohexanone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and propylene carbonate. For example, the solid content of the slurry is 65%. The slurry is coated on the current collector and dried. The surface density of the slurry is 200g / m 2 Up to 400g / m 2 The coated current collector is placed in a vacuum oven for drying at 85°C for 12 hours. Finally, an electrode sheet is obtained. The electrode material can be coated on one surface of the current collector or on two opposite surfaces of the current collector.

[0142] Of course, the surface density, solid content, drying temperature and time of the slurry are not limited to the above embodiments, and those skilled in the art can set them according to actual needs.

[0143] The electrode sheet has the characteristics of low internal resistance, good cycle performance and stable structure.

[0144] According to a third embodiment of the present application, a battery is provided, which includes the electrode sheet described in the present application.

[0145] The battery has the characteristics of low internal resistance, good cycle stability and good safety performance.

[0146] In one example, the electrode sheet is a positive electrode sheet, and the battery further includes a negative electrode sheet, a separator and an electrolyte, the separator is located between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet, the negative electrode sheet and the separator are immersed in the electrolyte.

[0147] In this example, the battery also includes a housing. The positive electrode sheet, the negative electrode sheet, and the separator are installed in the housing. Then, an electrolyte is injected into the housing so that the positive electrode sheet, the negative electrode sheet, and the separator are immersed in the electrolyte. The positive electrode sheet, the negative electrode sheet, and the separator form a stacked structure or a wound structure. Lithium ions are embedded and de-embedded between the positive electrode sheet and the negative electrode sheet to charge and discharge the battery.

[0148] Of course, the specific structure of the battery is not limited here, and those skilled in the art can configure it according to actual needs.

[0149] In one example, the electrolyte includes an electrolyte solvent, a lithium salt, and an additive, wherein the lithium salt and the additive are dissolved in the electrolyte solvent, and the additive includes fluoroethylene carbonate.

[0150] In this example, the electrolyte solvent is used to dissolve lithium salts and additives. The electrolyte solvent includes carbonate solvents, ether solvents, etc. Preferably, the electrolyte solvent includes: cyclic carbonates and chain carbonates. Cyclic carbonates have a higher redox stability window, can withstand the higher voltage generated by the battery during charging and discharging, and prevent decomposition under high voltage conditions or side reactions with electrode materials. Cyclic carbonates and chain carbonates have a higher dielectric constant, can better dissolve lithium salts, improve the ionic conductivity of the electrolyte, and thus improve the charging and discharging efficiency of the battery. During the first charge and discharge process, cyclic carbonates and chain carbonates can react with the surface of the positive and negative electrode materials of lithium metal or lithium ion batteries to generate a stable solid electrolyte interface film, thereby improving the cycle stability of the battery. Optionally, the cyclic carbonate includes at least one of ethylene carbonate and propylene carbonate. The chain carbonate includes at least one of dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate.

[0151] The lithium salt includes at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. Both of the above lithium salts have high electrical conductivity, thermal stability and chemical stability.

[0152] During the initial charging process, fluoroethylene carbonate can participate in the reaction on the surface of the negative electrode material to form a more stable and dense solid electrolyte interface film, namely SEI film. And participate in the reaction on the surface of the positive electrode material to form a stable and dense chemical-electrochemical interface film, namely CEI film. The SEI film can effectively passivate the surface of the electrode material, reduce the loss of active lithium, and prevent the electrolyte from further irreversibly reacting with the negative electrode active material, such as graphite, thereby enhancing the cycle stability of the battery. The CEI film can isolate and protect the positive electrode material, prevent the electrolyte from directly reacting with the positive electrode active material, thereby delaying the attenuation of the positive electrode material and improving the cycle stability of the battery. Fluorinated ethylene carbonate can also improve the conductivity of the electrolyte under low temperature conditions, making it easier for lithium ions to migrate at low temperatures, improving the charge and discharge performance and capacity retention rate of the battery in low temperature environments.

[0153] In one example, the additive further includes at least one of methylene methanedisulfonate, trimethylsilyl phosphate, triphenyl phosphate, vinylene carbonate, vinyl sulfate, and (ethoxy) pentafluorocyclotriphosphazene.

[0154] The above substances are stable in nature and can effectively improve the density of SEI and CEI films when used in combination with fluoroethylene carbonate, thereby effectively preventing harmful side reactions from occurring on the surfaces of positive and negative electrode materials and reducing the gas generation of positive and negative electrode materials. In addition, the above substances can improve the structural strength of SEI and CEI films.

[0155] Of course, the additives are not limited to the above embodiments, and those skilled in the art can configure them according to actual needs.

[0156] In one example, the additive further includes methylene methanedisulfonate, trimethylsilyl phosphate and triphenyl phosphate.

[0157] In this example, methylene disulfonate can promote the formation of a stable and conductive CEI film on the surface of the positive electrode material, reduce side reactions, improve the cycle stability of the battery, inhibit oxygen release, and enhance the thermal stability of the battery. Trimethylsilyl phosphate can improve the cycle performance and high temperature stability of the battery by forming a protective layer on the surface of the electrode material, such as SEI film and CEI film, reducing the side reactions of the electrolyte and the electrode active material, while improving the electrochemical window of the electrolyte. Triphenyl phosphate can form a stable SEI film, reduce the corrosion and side reactions of metallic lithium, and thus improve the cycle performance and safety of the battery.

[0158] Compared with the use of a single substance in combination with fluoroethylene carbonate, the use of the above three substances in combination with fluoroethylene carbonate can more effectively improve the density of the SEI film and the CEI film, thereby effectively preventing harmful side reactions from occurring on the surface of the positive and negative electrode materials and reducing the gas production of the positive and negative electrode materials.

[0159] Preferably, the mass percentage of each substance in the electrolyte is: methylene methanedisulfonate is 1% to 3%, trimethylsilyl phosphate is 0.5% to 1.5%, and triphenyl phosphate is 0.5% to 1.5%.

[0160] If the content of additives in the electrolyte is too much, the active lithium will be excessively consumed during the first charge and discharge cycle of the battery, forming a thicker or uneven SEI film and CEI film, resulting in an increase in the initial capacity loss of the battery. On the contrary, if the content of additives in the electrolyte is too little, the SEI film and CEI film formed may be incomplete, insufficient to effectively passivate the surface of the electrode material and prevent the electrolyte from further decomposing, which will lead to continuous side reactions, especially during the first charge and discharge process, which is easy to cause irreversible capacity loss. The electrolyte prepared within the above ratio range can make the SEI film and CEI film intact and ensure that the initial capacity loss of the battery is small.

[0161] In one example, the additive further includes vinylene carbonate, vinyl sulfate and (ethoxy) pentafluorocyclotriphosphazene.

[0162] In this example, during the initial charging process, vinylene carbonate is easily decomposed on the surface of the negative electrode to form a stable SEI film. The SEI film can effectively isolate the electrolyte from the negative electrode active material, prevent further decomposition of the electrolyte and precipitation of metallic lithium, thereby improving the cycle stability and safety of the battery.

[0163] Vinyl sulfate can improve the cycle performance and stability of lithium-ion batteries. Vinyl sulfate can form a sulfur-rich SEI film on the surface of the negative electrode active material. This film has good electrochemical stability and mechanical strength, can prevent the electrolyte from further decomposing, and can also promote the rapid transmission of lithium ions, thereby improving the cycle efficiency and service life of the battery.

[0164] Due to its fluorine-containing properties, the SEI film formed by (ethoxy) pentafluorocyclotriphosphazene has high thermal stability and electrochemical stability. (Ethoxy) pentafluorocyclotriphosphazene can not only inhibit the side reaction of the electrolyte on the surface of the electrode active material, but also enhance the adhesion between the electrolyte and the electrode material, which helps to improve the working performance and safety of the battery under high temperature conditions.

[0165] Compared with the use of a single substance in combination with fluoroethylene carbonate, the use of the above three substances in combination with fluoroethylene carbonate can more effectively improve the density of the SEI film, thereby effectively preventing harmful side reactions from occurring on the surface of the positive and negative electrode materials, reducing the gas production of the positive and negative electrode materials, and improving the working performance of the battery under high temperature conditions.

[0166] Preferably, the mass percentage of each substance in the additive is: vinylene carbonate is 0.5% to 1.5%, vinyl sulfate is 0.5% to 1.5%, and (ethoxy) pentafluorocyclotriphosphazene is 0.1% to 0.8%.

[0167] The electrolyte prepared within the above ratio range can make the SEI membrane and CEI membrane intact and ensure that the initial capacity loss of the battery is small.

[0168] According to a fourth embodiment of the present application, an electric device is provided, which includes the battery described in the present application.

[0169] The battery has the characteristics of good cycle performance, small internal resistance and good stability.

[0170] <Example>

[0171] (1) Preparation of positive electrode

[0172] The positive electrode material includes: electrode active material, point-shaped conductive material, linear conductive material, and binder. The electrode active material, point-shaped conductive material, linear conductive material, and binder are prepared in a mass ratio of 96:1.95:0.05:2. Among them, the core of the electrode active material is nickel-cobalt-manganese NCM523, and the main agent of the first coating layer is LiMn 0.4 Fe 0.6 PO4, LiMn 0.4 Fe 0.6 PO4 is doped with magnesium oxide, magnesium oxide and LiMn0.4 Fe 0.6 The molar ratio of PO4 is 3%, and the second coating layer is carbon black. The electric conductive material is carbon black. The linear conductive material is carbon nanotubes. The binder is polyvinylidene fluoride. The above-mentioned various materials are added into N-methylpyrrolidone and mixed to prepare positive electrode slurry. The solid content of the positive electrode slurry is 65%.

[0173] Then, the positive electrode slurry was prepared at a surface density of 300 g / m 2 The positive electrode slurry is evenly coated on the aluminum foil. The positive electrode slurry is coated on both surfaces of the aluminum foil to form an electrode sheet.

[0174] Next, the electrode sheet was dried in a vacuum oven at 85°C for 12 hours. The electrode sheet after drying had a density of 2.45 g / cm 3 The compaction density is rolled to obtain a positive electrode sheet.

[0175] (2) Preparation of negative electrode sheet

[0176] The negative electrode material package includes artificial graphite, carbon black, thickener, and binder. Artificial graphite, carbon black, thickener, and binder are prepared in a mass ratio of 95:1:1.5:2.5. Among them, the thickener is carboxymethyl cellulose. The binder is styrene-butadiene rubber. The above-mentioned various substances are added to deionized water and mixed to prepare negative electrode slurry. The solid content of the negative electrode slurry is 45%.

[0177] Then, the negative electrode slurry was prepared at a surface density of 145 g / m 2 The negative electrode slurry is evenly coated on the copper foil. Both surfaces of the copper foil are coated with the negative electrode slurry to form an electrode sheet.

[0178] Next, the electrode sheet was dried in a vacuum oven at 90° C. for 12 hours.

[0179] Finally, the dried electrode sheets were cut into strips and 3 The compaction density is cold pressed to obtain the negative electrode sheet.

[0180] (3) Preparation of electrolyte

[0181] The electrolyte includes an electrolyte solvent, a lithium salt, and an additive mixed together. The electrolyte solvent includes ethylene carbonate and ethyl methyl carbonate. The mass ratio of ethylene carbonate to ethyl methyl carbonate is 3:7. The lithium salt includes lithium hexafluorophosphate. The concentration of lithium hexafluorophosphate is 1.1 mol.

[0182] The additives include fluoroethylene carbonate, methylene methane disulfonate, trimethylsilyl phosphate and triphenyl phosphate, wherein, according to the mass percentage of the additives, fluoroethylene carbonate is 1%, methylene methane disulfonate is 2%, trimethylsilyl phosphate is 1% and triphenyl phosphate is 1%.

[0183] (4) Battery assembly, formation, and capacity division

[0184] The positive electrode sheet, the negative electrode sheet and the isolation film are assembled into a soft-pack battery. Among them, the isolation film is made of polypropylene. After the soft-pack battery is assembled, the electrolyte prepared as above is injected to obtain a soft-pack battery after injection. The capacity of the soft-pack battery is 10 ampere hours. The soft-pack battery is formed from 0.05C to 10% SOC, 0.1C to 30% SOC, and 0.2C to 60% SOC. After formation, a stable SEI film is formed on the negative electrode material. Excess gas generated during formation is discharged. The gas is extracted during secondary packaging. Then, it is charged to the upper limit voltage at 0.33C, and charged at a constant voltage to 0.05C cutoff, so that the positive electrode material forms a stable CEI film. Next, it is discharged at a constant current of 0.33C to the lower limit voltage to determine the battery capacity. The upper limit voltage is 4.35V. The lower limit voltage is 2.5V.

[0185] (5) Performance testing

[0186] The soft-pack batteries after capacity division are divided into groups, and the electrical performance of the batteries is tested using a lithium-ion battery charging and discharging system.

[0187] 1) 0.05C SOC-OCV test: At a constant temperature of 25°C, charge at a constant current of 0.05C to the upper limit voltage. Then discharge at a constant current of 0.05C to the lower limit voltage.

[0188] Depend on Figure 3 It can be seen that the charging curve and the discharging curve have good symmetry, indicating that the soft-pack battery can achieve stable constant current charging and discharging.

[0189] 2) SOC-DCIR test: The soft-pack battery is initially fully charged and discharged at a constant current of 0.33C to different SOCs, for example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%.

[0190] The DCIR test was performed at a temperature of 25°C. For charging DCIR, a 1.5C constant current was used to charge for 30 seconds to the upper voltage limit. After the test was completed, the battery was discharged at a 0.1C constant current to the power before the test. For discharging DCIR, a 1.5C constant current was used to discharge for 30 seconds to the lower voltage limit. After the test was completed, the battery was charged at a 0.1C constant current to the power before the test.

[0191] The comparative example uses LFMP, model DF-W6. The electrolyte model used in the comparative example is LBC338G. The negative electrode sheet and the separator are the same as those used in the embodiment of the present application.

[0192] Depend on Figure 4 It can be seen that the SOC-DCIR curve of the battery of the comparative example has a spike when the SOC is 40%, indicating that the internal resistance of the battery of the comparative example is large in this state, and it is easy to reach the upper limit voltage, which causes charging to stop and the battery capacity is small. However, the battery of the embodiment of the present application does not have a spike when the SOC is 40%, and the SOC-DCIR curve of the battery of the embodiment of the present application is generally below the SOC-DCIR curve of the battery of the comparative example. Therefore, the internal resistance of the soft-pack battery of the embodiment of the present application is small, it is not easy to reach the upper limit voltage, and the capacity of the soft-pack battery is large.

[0193] 3) Rate charge and discharge test:

[0194] Rate discharge: At a constant temperature of 25°C, charge to the upper limit voltage at a constant current and voltage of 0.33C, and the cut-off current is 0.05C. The soft-pack battery is discharged to the lower limit voltage at a constant current of 0.33C, 0.5C, 1.0C, 2.0C, 3.0C, and 4.0C.

[0195] Rate charging: Discharge at a constant current of 0.33C to the lower limit voltage, and charge the battery at a constant current of 0.33C, 0.5C, 1.0C, 2.0C, 3.0C, and 4.0C to the upper limit voltage.

[0196] Depend on Figure 5 It can be seen that the charging energy retention rate of the soft-pack battery in the embodiment of the present application can reach 96.2% at 4.0C. However, the charging energy retention rate of the battery in the prior art is below 90% at 4.0C. It can be seen that the soft-pack battery in the embodiment of the present application has a high charging energy retention rate.

[0197] The discharge energy retention rate of the soft-pack battery of the embodiment of the present application can reach 94.5% at 4.0 C. However, the discharge energy retention rate of the battery of the comparative example is below 90% at 4.0 C. It can be seen that the soft-pack battery of the embodiment of the present application has a high discharge energy retention rate.

[0198] And as the charge and discharge rates decrease, the charge retention rate and discharge retention rate gradually increase.

[0199] 4) Discharge test at different temperatures: At a constant temperature of 25°C, charge to the upper limit voltage at a constant current and constant voltage of 0.33C, and the cut-off current is 0.05C. The soft pack battery is discharged to the lower limit voltage at a constant current of 0.33C at different temperatures, for example, 45°C, 35°C, 25°C, 10°C, 0°C, -10°C, -20°C, -25°C, and -30°C.

[0200] Depend on Figure 6 It can be seen that as the ambient temperature decreases, the capacity retention rate and energy retention rate of the soft-pack battery both decrease. When the ambient temperature is above 0°C, the capacity retention rate and energy retention rate of the battery are both high.

[0201] The above embodiments focus on the differences between the various embodiments. As long as the different optimization features between the various embodiments are not contradictory, they can be combined to form a better embodiment. Considering the simplicity of the text, they will not be repeated here.

[0202] Although some specific embodiments of the present invention have been described in detail by way of example, it will be appreciated by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present invention. It will be appreciated by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.

Claims

1. An electrode material, characterized in that: The invention comprises an electrode active material, wherein the electrode active material comprises an inner core (1) containing a nickel-cobalt-manganese material, a first coating layer (2) coated outside the inner core (1), and a second coating layer (3) coated outside the first coating layer (2), wherein the first coating layer (2) comprises a transition metal-doped lithium manganese iron phosphate material, and the second coating layer (3) comprises a conductive agent.

2. The electrode material according to claim 1, characterized in that: The first coating layer (2) comprises a conductive agent, and the transition metal-doped lithium manganese iron phosphate material is mixed with the conductive agent.

3. The electrode material according to claim 2, characterized in that: Along the thickness direction of the electrode active material, the concentration of the transition metal-doped lithium manganese iron phosphate material in the first coating layer (2) gradually decreases from a side close to the core (1) to a side close to the second coating layer (3).

4. The electrode material according to claim 1, characterized in that: The transition metal oxide includes a divalent transition metal oxide.

5. The electrode material according to claim 4, characterized in that: The divalent transition metal oxide includes at least one of beryllium oxide, magnesium oxide and calcium oxide.

6. The electrode material according to any one of claims 1 to 5, characterized in that: The conductive agent includes a carbon material.

7. The electrode material according to claim 6, characterized in that: The carbon material includes at least one of a point-shaped carbon material and a linear carbon material.

8. The electrode material according to claim 1, characterized in that: The molar ratio of manganese to iron is x:(1-x), wherein x=0.3 to 0.

9.

9. The electrode material according to claim 1, characterized in that: In the transition metal-doped lithium manganese iron phosphate material, the molar ratio of the transition metal oxide to the lithium manganese iron phosphate material is 0.1% to 10%.

10. The electrode material according to claim 1, characterized in that: Also includes: A conductive material is mixed with the electrode active material.

11. The electrode material according to claim 10, characterized in that The conductive material includes linear conductive material and dot conductive material.

12. The electrode material according to claim 11, characterized in that In parts by mass, the electrode active material is 90 parts to 97 parts, the point-shaped conductive material is 1.8 parts to 2 parts, the line-shaped conductive material is 0.02 parts to 0.2 parts, and the binder is 1 part to 3 parts.

13. The electrode material according to claim 1, characterized in that The density of the electrode material is 2.3 g / cm 3 Up to 2.6g / cm 3 .

14. An electrode sheet, characterized in that: The invention comprises a current collector and the electrode material according to any one of claims 1 to 13, wherein the electrode material is attached to the surface of the current collector.

15. A battery, characterized in that: Comprising the electrode sheet as claimed in claim 14.

16. The battery according to claim 15, characterized in that: The electrode sheet is a positive electrode sheet, and the battery further comprises a negative electrode sheet, a separator and an electrolyte. The separator is located between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet, the negative electrode sheet and the separator are immersed in the electrolyte.

17. The battery according to claim 16, characterized in that: The electrolyte includes an electrolyte solvent, a lithium salt and an additive, wherein the lithium salt and the additive are dissolved in the electrolyte solvent, and the additive includes fluoroethylene carbonate.

18. The battery according to claim 17, characterized in that: The additive further comprises at least one of methylene methanedisulfonate, trimethylsilyl phosphate, triphenyl phosphate, vinylene carbonate, vinyl sulfate, and (ethoxy) pentafluorocyclotriphosphazene.

19. The battery according to claim 17, characterized in that: The additives also include methylene methanedisulfonate, trimethylsilyl phosphate and triphenyl phosphate.

20. The battery according to claim 19, characterized in that: The mass percentages of the various substances in the electrolyte are: methylene methanedisulfonate is 1% to 3%, trimethylsilyl phosphate is 0.5% to 1.5%, and triphenyl phosphate is 0.5% to 1.5%.

21. The battery according to claim 17, characterized in that: The additives also include vinylene carbonate, vinyl sulfate and (ethoxy) pentafluorocyclotriphosphazene.

22. The battery according to claim 21, characterized in that: The mass percentages of the various substances in the electrolyte are: vinylene carbonate is 0.5% to 1.5%, vinyl sulfate is 0.5% to 1.5%, and (ethoxy) pentafluorocyclotriphosphazene is 0.1% to 0.8%.

23. The battery according to claim 17, characterized in that: The electrolyte solvent includes cyclic carbonate and chain carbonate.

24. The battery according to claim 23, characterized in that: The cyclic carbonate includes at least one of ethylene carbonate and propylene carbonate.

25. The battery according to claim 23, characterized in that: The chain carbonate includes at least one of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.

26. An electrical equipment, characterized in that: Comprising a battery as claimed in any one of claims 15 to 25.